Analyze The Role Of Social Media In Increasing Customer Loyalty In Shopee's Digital E-Commerce Business - Amelia Amelia; Sukma Hendrian; Mar'atus Solikhah; Siti Ainul Kholipah; Rendi Brahma Fahrezi (Jurnal Indonesia Sosial Teknologi, 2023)
The development of information technology, especially social media, has brought significant changes in the way businesses operate and interact with customers. In the era of digital business, social media has become one of the important tools in building digital business loyalty with its customers. The purpose of this study is to analyze the role of social media in increasing customer loyalty in digital businesses. This research uses qualitative research methods. The data collection technique was carried out by a literature study obtained from Google Scholar and social media from Shopee’s E-commerce digital business. The data that has been collected is then analyzed thematically. The results showed that social media plays a role in increasing customer loyalty by increasing customer satisfaction and service quality through customer interaction, promotional media, offering gifts, and sharing interesting content.